The Islamic veil as a cause for dismissal in private companies - Leal-Adorna, Mar (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
The use of religious symbols in the labor environment has resulted in problems not only at the national level, but also at the European and international levels. In many cases, the courts have taken positions on whether or not the firing of an employee for wearing clothing or symbols representative of a given religious confession constitutes religious discrimination. This study explores whether or not a right to wear religious symbols actually exists, analyzes the legislation and regulations (or lack thereof) surrounding that question, and delves into the specific cases that have resulted in legal decisions being made pertaining to the termination of private-sector employment due to a person’s decision to wear the Islamic veil.
Keywords: Islamic veil; laboral firing; religious freedom; religious discrimination